O constitucional e o real da política regularização territorial quilombola: uma análise da comunidade de Caiana dos Crioulos –Alagoa Grande/PB - Silvestre, Diego de Oliveira (2015)
The issue of quilombo territories, presents as a trigger for debate since the enactment of the Constitution of 1988 -CF88, creating a space of struggle and negotiation around the national project. In this sense,the recognition of the territories position different sectors and interests and become visible antagonisms and conflicts within the Brazilian society. The land regularization process of quilombo communities, made possible by Article 68 of the ADCT, enabled the emergence of organized collective identities. However, most Brazilians, especially public officials, still have little understanding of who really are these quilombo communities and generally comprising them even as groups that rebelled against slavery through leaks and creating quilombos distant, overlapping so the ethnic group idea. Thus, the aim of this study is to analyze the effectiveness of territorial recognition policies of maroon communities in the state of Paraiba, taking as spatial area Caiana of Crioulos the community -Alagoa Grande, as well as their socio-economic consequences for it. The results show that the vast bureaucracy, especially with regard to lot of judicial resources filed by the "owners" of the land required by the quilombolas, hold back the progress of the land regularization process of the community. We found that all contrary or favorable actions quilombo communities, held in institutional spheres of our country, either in Congress, the INCRA, in FCP, in INTERPAs, etc. direct impact on communities, thus causing direct consequences on its residents, and Caiana of Crioulos, was not (or is) different, higher levels of actions has led residents to put into play to stay in the community, endangering the history and community culture. Therefore the migration of entire families, increasingly recurrent becomes, characterizing the neglect and giving up the struggle for land.